Spontaneous coronary artery dissection in a male with ischemic stroke: A case report with brief review of literature - Ete, Tony; Saha, Swapan; Mobing, Habung; Naku, Narang; Kumar, Arun; Fanai, Vanlalmalsawndangliana; Bamon, Amethyst; Khan, Shakeel Ahamad; Kumar, Utpal; Mishra, Animesh (Indian Journal of Case Reports, 2020)
Spontaneous coronary artery dissection (SCAD), also referred to as SCAD, is an uncommon emergency condition that occurs when a tear forms in a blood vessel in the heart. SCAD has emerged as an important cause of acute coronary syndrome, myocardial infarction, and sudden cardiac death, particularly among individuals with few conventional atherosclerotic risk factors and young women. It is usually seen in females with pre-existing conditions such as connective tissue disease, systemic lupus erythematosus, and the puerperium. Commonly, the patient presents with acute-onset severe chest pain coupled with autonomic symptoms such as diaphoresis, palpitations, and hypotension. SCAD presenting with ischemic stroke in a male patient is extremely rare. Hereby, we present a case of SCAD in a middle-aged gentleman who strangely presented with ischemic stroke.